FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI INDUSTRI KECIL SULAMAN DI PROVINSI SUMATERA BARAT - Aizat, Aninda; Sentosa, Sri Ulfa (Universitas Negeri Padang, 2020)
Abstract :This study.aim to examine of the factors that influence the production ofsmall embroidery industries in West Sumatra Province with the Fixed Effect Model(FEM) selected. The data used is panel data during the 2014-2018 period, withdocumentation data collection techniques and literature study obtained from relatedinstitutions and agencies. The variables used are Capital (X1), Labor (X2) andBusiness Units (X3). The research method used is: OLS. estimation results show thecapital has positive, insignifican. Effect.on embroidery production in West Sumatra.Furthermore, Labor has a negative and insignificant effect on embroideryproduction in West Sumatra. And the business unit has a positive and significanteffect on embroidery production in West Sumatera. Together., capital, labor andbusiness units have a significant effect on embroidery production in West Sumatra.Keywords: Capital, Labor, Business Units, Production, and Ordinary Least Square(OLS).